Molecular alterations of newly formed mandibular bone caused by zoledronate. Issue 9 (September 2018) - Yoshioka, Y.; Yamachika, E.; Nakanishi, M.; Ninomiya, T.; Nakatsuji, K.; Matsubara, M.; Moritani, N.; Kobayashi, Y.; Fujii, T.; Iida, S.
Abstract: Bone quality is defined by structural and material characteristics. Most studies on the mandible have focused on the analysis of structural characteristics, with insufficient investigation of material characteristics. This study tested whether zoledronate affects the material characteristics of newly formed mandibular bone. Thirty-six female Wistar rats were assigned to three groups: sham-ovariectomized rats (SHAM, n = 12), ovariectomized rats (OVX, n = 12), and ovariectomized rats treated with zoledronate (ZOL, n = 12). The left side of the mandibular ramus of all rats was drilled bicortically. Twenty-eight days after surgery, all surviving rats were euthanized and all mandibles were removed. Raman microspectroscopy was performed, and five spectra per specimen of newly formed mandibular bone were analysed. Compared with OVX rats, the mineral/matrix ratio in ZOL rats was significantly increased (5.43 ± 1.88 vs. 7.86 ± 2.05), while crystallinity (0.055 ± 0.002 vs. 0.050 ± 0.002), relative proteoglycan content (0.43 ± 0.10 vs. 0.31 ± 0.05), and collagen structural integrity (1.16 ± 0.21 vs. 0.72 ± 0.06) were significantly decreased. These changes in material characteristics may explain why rats that received zoledronate exhibited peculiar biological phenomena such as bisphosphonate-related osteonecrosis of the jaw.